Effect of intraperitoneal chemotherapy and peritoneal lavage in positive peritoneal cytology in gastric cancer. Systematic review and meta-analysis. Issue 9 (September 2016) - Coccolini, F.; Catena, F.; Glehen, O.; Yonemura, Y.; Sugarbaker, P.H.; Piso, P.; Ceresoli, M.; Montori, G.; Ansaloni, L.
Abstract: Introduction: The most common cause of tumour progression in advanced gastric cancer is peritoneal carcinosis (PC). The necessity to increase the survival in advanced diseases suggested to deliver the chemotherapy directly in the peritoneal cavity also in Cy+/PC− and to experiment the effect of massive peritoneal lavage to wash out the tumour cells. The aim of this study is to investigate the gain in term of survival and peritoneal recurrence rate of the intraperitoneal chemotherapy and/or peritoneal lavage in patients with Cy+/PC−. Material and methods: A systematic review with meta-analysis of trials about the effect of intraperitoneal chemotherapy (IPC) and/or peritoneal lavage (PL) on positive cytology in gastric cancer without carcinosis. Results: Three trials have been included (164 patients: 76 received surgery alone, 51 surgery + IPC and 37 surgery + IPC + PL). Two- and five-years survival is increased by IPC (RR = 1.62, RR = 3.10). 2 and 5 years survival is further increased by IPC + PL (RR = 2.33, RR = 6.19). Peritoneal recurrence is reduced by IPC (OR = 0.45) and by IPC + PL (OR = 0.13). Conclusions: Two- and five-years overall survival in patients with free cancer cells without carcinosis is incremented by intraperitoneal chemotherapy. Peritoneal lavage further increases these survival rates and also it further decreases the peritoneal recurrence rate.